High-voltage electrical burns: five-year epidemiological analysis and updated surgical treatment - Thiago Henrique Tondineli; Juan Alfredo Sanabria Rios; Karem Candelario; Ricardo Cavalcanti Ribeiro; Luiz Maceira Junior; Maria Cristina do Valle Freitas (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Evaluation of a 5-year epidemiological analysis and updated surgical treatment of high-voltage electrical burns. METHODS: A descriptive, retrospective cross-sectional study was conducted in the Center of Burn Treatment Dr. Oscar Plaisant, Federal Hospital of Andaraí, Rio de Janeiro, Brazil, from January 2009 to December 2014. A form was applied to the medical records of 38 patients included in the study in order to assess the defined variables. RESULTS: In total, 38 patients with high-voltage burns were evaluated, 95% of whom were men aged between 21 and 42 years. The most frequent place of occurrence was the workplace in 55.3% of cases. The percentage of burned total body surface area ranged from 1% to 60%. The most affected part of the body was the left hand in 55.26% cases. Presurgical preparation for self-grafting was necessary in 34.21% subjects, and the mean time elapsed was 37.5 days. The type of surgical treatment was serial debridement under general anesthesia in 100% of the patients, self-grafting in 31.6%, amputation in 18.4%, and fasciotomy in 5.3%. The mortality rate was 0%. CONCLUSIONS: The study indicated that electrical burns occur most often in young adults in the workplace; therefore, policies should be developed to raise safety awareness in the workplace. Despite the severity of the injury, patients with adequate clinical support and early surgical evaluation are more likely to survive, even with high rates of amputation, confirming the need for more research on electroporation.